2002
DOI: 10.1557/proc-713-jj11.55
|View full text |Cite
|
Sign up to set email alerts
|

Alteration-Phase formation and Associated Cesium Release During Alteration of R7T7 Waste Glass

Abstract: Static corrosion tests were performed with an inactive HLW glass of R7T7 type in order to evaluate alteration-phase formation and associated Cs release during the glass corrosion. The tests were performed in NaOH solutions at elevated temperatures in order to accelerate the corrosion. Crystalline phases formed in the corroded glass were analyzed by use of XRD, in addition to the solution analysis. The results indicated that; 1)Analcime or Na-beidellite or both of them form during the corrosion depending on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Effect of sodium. pH is buffered by NaOH additions in this study and by KOH additions in the one of Gin and Mestre (2001) and sodium seems to slightly favor resumption of alteration compared to potassium , Inagaki et al, 2002, Inagaki et al, 2006, possibly because of the important "structure-forming" function of Na + during zeolite precipitation (Liu et al, 2014). Effect of pH stability.…”
Section: Testmentioning
confidence: 63%
“…Effect of sodium. pH is buffered by NaOH additions in this study and by KOH additions in the one of Gin and Mestre (2001) and sodium seems to slightly favor resumption of alteration compared to potassium , Inagaki et al, 2002, Inagaki et al, 2006, possibly because of the important "structure-forming" function of Na + during zeolite precipitation (Liu et al, 2014). Effect of pH stability.…”
Section: Testmentioning
confidence: 63%
“…Inagaki also demonstrated that solution pH and solution concentrations of Na and K were involved in the formation of analcime vs Na‐beidellite (a smectite clay). Other phases such as smectite clays that are rich in Fe 3+ compared to Al 3+ do not appear to accelerate glass corrosion .…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Two different glasses were studied, SM58 that contained 1. [126] demonstrated that solution pH and solution concentrations of Na and K were also involved in the formation of undesirable analcime versus Na-bedellite (a smectite clay). Other zeolites and smectite clays that are rich in Fe 3+ compared to Al 3+ do not appear to accelerate glass corrosion [110,127,128].…”
Section: Stages Of Corrosionmentioning
confidence: 99%